Evaluating monetary policy effectiveness in North Macedonia: Evidence from a Bayesian FAVAR Framework - Magdalena Petrovska; Jasna Tonovska; Miso Nikolov; Artan Sulejmani (National Bank of the Republic of North Macedonia, 2023)
This paper has adopted a Bayesian FAVAR approach to examine the monetary transmission mechanism in North Macedonia. The model is based on a broad data set that encompasses 140 monthly time series spanning between January 2010 and January 2019. In particular, the impact of policy on bank portfolio variables, and the impact of policy on economic activity variables have been evaluated. Our findings show that monetary tightening, causes a fall in output, inflation rate, employment, bank lending, the stock of government securities held by banks, and equity prices. On the other hand, it increases shortterm money market rates, lending rates, deposits, and only in the immediate aftermath of the key policy rate rise, the share of non-performing loans in the loan portfolio. The study is expected to provide useful input to monetary policy implementation in North Macedonia. The study as well enriches the literature in this domain by discussing the challenges facing monetary authorities of small open economies with fixed exchange rate regimes in understanding how their policy instruments work through the economy
Keywords: E52; E47; 330; Monetary transmission mechanism; FAVAR; Bayesian estimation; Monetary policy